2020
DOI: 10.1097/ijg.0000000000001703
|View full text |Cite
|
Sign up to set email alerts
|

Deep Sclerectomy With Intrascleral Versus Suprachoroidal Collagen Implant: A Randomized Control Trial

Abstract: Précis: Deep sclerectomy with intrascleral collagen implant (DSCI) was less effective in lowering intraocular pressure (IOP) than with suprachoroidal implantation. Further studies are needed to establish the potency and safety of deep sclerectomy with suprachoroidal collagen implant (DSSCI). Purpose: The purpose of this study was to analyze the safety and IOP-lowering effect of DSSCI in comparison with DSCI. Setting: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 12 publications
0
7
0
1
Order By: Relevance
“…This is indirectly supported by our observations in cases where a classical DS was performed (with the creation of a trabeculo-Descemet’s window without a laser trabeculotomy) with placement of a CI as described above, where LV were observed on slit lamp examinations with a significant decrease in IOP. Mitwally et al [ 23 ] also demonstrated a greater IOP-lowering effect of DS with suprachoroidal CI than with DS and intrascleral implantation. The role of the implantation of a non-absorbable collagen implant (Xenoplast, Dubna-Biofarm, Moscow, Russia) in the SCS in decreasing IOP has been studied by Shradka A.S. et al [ 24 ] and Kumar V. et al [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…This is indirectly supported by our observations in cases where a classical DS was performed (with the creation of a trabeculo-Descemet’s window without a laser trabeculotomy) with placement of a CI as described above, where LV were observed on slit lamp examinations with a significant decrease in IOP. Mitwally et al [ 23 ] also demonstrated a greater IOP-lowering effect of DS with suprachoroidal CI than with DS and intrascleral implantation. The role of the implantation of a non-absorbable collagen implant (Xenoplast, Dubna-Biofarm, Moscow, Russia) in the SCS in decreasing IOP has been studied by Shradka A.S. et al [ 24 ] and Kumar V. et al [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…While the trabecular outflow pathway, which involves a subconjunctival bleb formation, has been studied for several years, lately attention has been directed to the uveoscleral pathway, which involves aqueous bleb-less drainage 47. This has meant a lower risk of DS failure with uveoscleral implants compared with scleral devices, due to increased aqueous outflow through the suprachoroidal pathway and also due to the lower rate of complications related to the subconjunctival bleb 33,47. On the other hand, a significant limiting factor in the long-term success of DS with uveoscleral implants is the inflammatory potential of the suprachoroidal region characterized by significant cell infiltration and fibrosis 33,47,48.…”
Section: Discussionmentioning
confidence: 99%
“…47 This has meant a lower risk of DS failure with uveoscleral implants compared with scleral devices, due to increased aqueous outflow through the suprachoroidal pathway and also due to the lower rate of complications related to the subconjunctival bleb. 33 , 47 On the other hand, a significant limiting factor in the long-term success of DS with uveoscleral implants is the inflammatory potential of the suprachoroidal region characterized by significant cell infiltration and fibrosis. 33 , 47 , 48 This deficiency could be resolved by using materials with better modulation of biological responses, inducing minimal tissue reaction and scarring, especially in the suprachoroidal region.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Несмотря на это, во всех 3 случаях мы наблюдали лимфатические сосуды при обследовании на щелевой лампе пациентов со значительным снижением уровня ВГД. R. Mitwally et al [19] продемонстрировали больший эффект снижения ВГД при глубокой склерэктомии с супрахориоидальным коллагеновым имплантатом, чем при глубокой склерэктомии с интрасклеральной имплантацией коллагенового имплантата. Примечательно, что в предложенной методике экспозиция поверхности увеальной ткани для резорбции ВВ была увеличена путем дополнительного удаления полоски глубоких слоев склеры сзади от склерального мостика.…”
Section: клиническая практикаunclassified